PELATIHAN PRODUKSI JAHE INSTAN IBU-IBU DI RT. 12 - RW. 03 KELURAHAN MULYOREJO KECAMATAN SUKUN KOTA MALANG - Koesmarijanto; Hudiono; Nugroho Suharto; Aad Hariyadi (Jurnal Pengabdian Polinema Kepada Masyarakat, 2020)
Ginger is a type of spice that is widely used traditionally as a medicine. The content of essential oils and oleoresin in ginger has antibacterial activity. Today many foods and drinks are offered as supplement products that can improve body health if consumed. Health drinks are drinks that contain elements of nutrients or non-nutrients and if consumed can have a positive influence on body health. Health drinks as one of the products that are well known to the public, are often found on the market with various brands and forms, such as liquid, instant powder or tablets. This activity aims to provide alternative skills for PKK RT mothers. 12 - RW. 03 Mulyorejo Village, Sukun District, Malang City, can develop entrepreneurship in products made from ginger. Each participant of this activity knows how to use ginger for making instant drinks and brings the results of training in the form of instant ginger. The community service activities that have been carried out have provided many benefits, especially adding broader insights in understanding the concept of food business development, especially in the use of ginger and applying the theory of extraction and crystallization in the manufacture of instant drinks. This community service activity can be used as a new opportunity to develop entrepreneurship..